Por que razão se vão embora? Análise de uma teoria implícita da rotação pessoal através da técnica do mapeamento cognitivo - Nunes, Francisco Guilherme Serranito (1995)
The aim of the present paper is to analyze the content and structure of an implicit theory put forward by a group of technicians to account for employees leaving the organization the used to work for, comparing it with well known extant scientific models. The author makes both use of the concept of cognitive map, and of mapping techniques advanced by Bougon (1977,1983).